2001
DOI: 10.1002/jmv.2044
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus strains circulating in Ethiopia in 1998–1999: Molecular characterisation using oral fluid samples and identification of a new genotype

Abstract: A measles outbreak in December 1998 in Bedelle (vaccine coverage <40%) and two sporadic cases in Addis Ababa, Ethiopia, were investigated. Paired serum and oral fluid samples were collected 2-8 days after the onset of symptoms. A total of 53 of 55 outbreak cases and both sporadic cases were positive for serum measles virus-specific IgM. Oral fluid measles-specific IgM was positive in 71% of cases collected up to 5 days after onset and in 90% collected at 6-8 days. By contrast, 100% of oral fluid samples were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 29 publications
1
45
1
Order By: Relevance
“…The identification of genotype D8 in 1999-2000 is more interesting because importations from south Asia, the Middle East, and the Balkans were associated with this genotype at that time. The same type was identified in Ethiopia in 1998-1999 [21], and some importations may reflect the increase in measles observed during 1998 in both the African and Eastern Mediterranean regions [18]. Although genotyping has been useful in describing measles diversity, we have not been able to attribute all of the less common genotypes to importation from specific regions.…”
Section: Discussionmentioning
confidence: 96%
“…The identification of genotype D8 in 1999-2000 is more interesting because importations from south Asia, the Middle East, and the Balkans were associated with this genotype at that time. The same type was identified in Ethiopia in 1998-1999 [21], and some importations may reflect the increase in measles observed during 1998 in both the African and Eastern Mediterranean regions [18]. Although genotyping has been useful in describing measles diversity, we have not been able to attribute all of the less common genotypes to importation from specific regions.…”
Section: Discussionmentioning
confidence: 96%
“…Oral fluids can also be used to detect viral ribonucleic acid (RNA) and their use is becoming increasingly common because samples can be obtained safely and non-invasively, without the risks associated with blood collection, and it improves patient compliance with specimen collection, as the procedure is simple and painless. [7][8][9][10] Point-of-care tests (POCTs) are increasingly used for the rapid diagnosis of infections. They can be performed in a single incubation step at ambient temperature without complex electrical equipment and their results can be read visually.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, clade D viruses appear to circulate endemically in the southern and eastern parts of the African continent. Endemic circulation of genotypes D2 and D4 has been shown in South Africa, Namibia, Zimbabwe, and Kenya, while genotypes D4 and D8 have been reported from as far north as Ethiopia [Kreis et al, 1997;Nigatu et al, 2001;Mbugua et al, 2003;Rota and Bellini, 2003]. Characterization of MVs from an outbreak in Morocco in 1998/1999 showed that they were genotype C2, which suggests that Northern Africa may be linked to European transmission patterns rather than to African patterns [Alla et al, 2002].…”
Section: Introductionmentioning
confidence: 92%